2020
DOI: 10.29309/tpmj/2020.27.05.4278
|View full text |Cite
|
Sign up to set email alerts
|

Different tumour grading in smokeless tobacco (Naswar) user and non-user in squamous cell carcinoma.

Abstract: Objectives: To determine the relationship of Naswar with different tumour grading in squamous cell carcinoma. Study Design: Comparative cross-sectional study using non-probability, consecutive sampling. Setting: Department of Oral Pathology, Rehman College of Dentistry, Peshawar, Khyber Pakhtunkhwa, Pakistan. Period: January 2017 till June 2017. Material & Methods: 60 cases of oral squamous cell carcinoma were included. Half the cases (30) had a history of Naswar use while the other half (30) had no histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In this research had found that the majority of the cases were well differentiated (52.4%), followed by Moderately Differentiated cases (27.2%) and then poorly differentiated cases (20.4%). In accordance with our study Sarfaraz et al, 2020 showed well differentiated to be the most common grade for OSCC cases (19). Contrary to our Results Mehdi et al, 2019 from Pakistan showed same number of moderately differentiated and poorly differentiated cases and slightly less number of well differentiated cases (20).…”
Section: Resultssupporting
confidence: 91%
“…In this research had found that the majority of the cases were well differentiated (52.4%), followed by Moderately Differentiated cases (27.2%) and then poorly differentiated cases (20.4%). In accordance with our study Sarfaraz et al, 2020 showed well differentiated to be the most common grade for OSCC cases (19). Contrary to our Results Mehdi et al, 2019 from Pakistan showed same number of moderately differentiated and poorly differentiated cases and slightly less number of well differentiated cases (20).…”
Section: Resultssupporting
confidence: 91%
“…Naswar is a combination of crushed tobacco leaves, slaked lime, and ashes, which is either inhaled or dipped in the vestibule of either side. After 5 min, the nicotine-associated products seep into the inner mucosa and exhibit a slight burning and numbing sensation [ 21 ]. The effect is mainly due to the high pH of un-ionized nicotine as well as tobacco-specific N-nitrosamines (TSNAs), which are carcinogenic and genotoxic.…”
Section: Discussionmentioning
confidence: 99%